The new Silk Road leads through the Arab Peninsula : mastering global business and innovation - Visvizi, Anna; Lytras, Miltiadis D.; Alhalabi, Wadee; Zhang, Xi (Emerald Publishing Limited, 2019)
Building on the tradition, promises and advances brought by the historical Silk Road, the Belt and Road Initiative launched by Chinese authorities in 2013 has the potential to re-draw the map of checks and balances in the global economy. The New Silk Road leads through the Arab Peninsula: Mastering Global Business and Innovationoffers an in-depth inquiry into the origins, implications, opportunities and synergies that China's Belt and Road Initiative creates for stakeholders in both Asia and the Arab World.Acclaimed academics, practitioners and experts contribute to a fascinating overview of critical issues that emerge along the New Silk Road. Chapters address issues such as dispute resolution, the geopolitics of international business, the enabling role of sophisticated technologies, approaches to innovation promotion and cross-cultural collaboration. Case-studies featuring specific businesses and industries operating in the Belt and Road context further add to the empirical focus that this book offers.An essential resource for graduate and executive education in a range of fields, including international business, international political economy, strategic management, and appliedcomputer science, this volume will also serve as an illuminating study for anyone interested in contemporary global affairs.